A method of SQL access logs pretreatment for power business system - Weiwei LI; Tao ZHANG; Yuanyuan MA; Cheng ZHOU (Dianxin kexue)
With the development of smart grid interactive,the database interaction between the information inside and outside is increasing.A method of SQL access log compression for power business system to respond to the demand of database security audit for the power system was designed in detail.This method can realize the compression of SQL access log and have the function of simple classification for SQL logs.The test results show that the method can achieve a large margin compression of SQL access logs and meet the requirements of log preprocessing for the database behavior audit of power business system.